Morphometric characteristics of changes in the anterior abdominal wall muscles after implantation of polypropylene meshes of different types in experiment - V. I. Piatnochka (Kazimierz Wielki University, 2018)
A widespread introduction of modern alloplastic materials into the surgical practice has significantly improved the results of surgical treatment of the patients with ventral and postoperative ventral hernia. However, the implantation of synthetic material into the anterior abdominal wall tissues is accompanied by different local reactions, especially when using 'heavyweight' meshes that often cause development of complications. The analysis of the results determines the topical issue of this study. Objective. The aim of the study was to conduct a morphometric evaluation of changes in the anterior abdominal wall muscles after the implantation of 'heavy' and 'light' polypropylene meshes as well as 'light' ones in combination with the PRF membrane. Materials and methods. Morphometric study involved analysis of anterior abdominal wall muscles after implantation of 'heavy', 'light' polypropylene meshes, as well as the 'light' ones in combination with the PRF membrane, into the retro-muscular space in light-optical investigation of microslides. The experiments were carried out on 18 mature male Vietnamese pigs, which were divided into 6 groups. Results. In the group of animals 2m significant structural changes of muscles were revealed. The diameter of myocytes increased from (13.50±0.15) to (14.20±0.18) µm. These morphometric parameters statistically significantly (p